Cointegration between Macroeconomic Variables and Stock Market Returns in Nepal - Rana, Surya Bahadur (Journal of Business and Social Sciences Research, 2021)
This paper examines the long-run relationship between selected macroeconomic variables and the stock market returns in Nepal over 1995-2020 periods. Based on the ARDL bounds testing approach, the study reveals significant long-run positive impact of real GDP growth, and negative impact of exchange rate and inflation on stock market returns in Nepal. The result of error correction representation shows that any short-run disequilibrium among the variables tends to return to their long-run equilibrium with speed of adjustment of 47.57 percent in a year. The study results imply that policy makers should come up with policies to accelerate the pace of economic growth and should initiate export stimulating policies to ensure the positive impact on stock market. Finally, the study results also suggest that controlled and stabilised interest rate environment enhances depth and breadth of stock market trading by attracting significant number of prospective investors demanding more investments in stock market of Nepal.